2014
DOI: 10.1007/s10552-014-0510-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for endometrial cancer in black and white women: a pooled analysis from the epidemiology of endometrial cancer consortium (E2C2)

Abstract: Purpose Endometrial cancer (EC) is the most common gynecologic cancer in the United States. Over the last decade, the incidence rate has been increasing, with a larger increase among blacks. The aim of this study was to compare risk factors for EC in black and white women. Methods Data from 7 cohort and 4 case-control studies were pooled. Unconditional logistic regression was used to estimate adjusted odds ratios (OR) and 95% confidence intervals for each risk factor in blacks and whites separately. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…1,44,45 In addition, far less is known about their etiology. In a 2013 report from the Gynecologic Oncology Group trial, which included 2,244 type I endometrial cancers and 581 type II endometrial cancers from 62 U.S. institutions, type II endometrial cancer was positively associated with multiparity and smoking, and inversely associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…1,44,45 In addition, far less is known about their etiology. In a 2013 report from the Gynecologic Oncology Group trial, which included 2,244 type I endometrial cancers and 581 type II endometrial cancers from 62 U.S. institutions, type II endometrial cancer was positively associated with multiparity and smoking, and inversely associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies of reproductive history and endometrial cancer have been conducted among white women [20]. The generalizability of these findings to other racial and ethnic groups is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent SEER data show increases in incidence in black women, for serous, clear cell, and endometrioid subtypes. Pooled data from E2C2 have shown that risk factors for endometrial cancer are similar in both racial groups [17]; although this is the largest study to date of risk factors in black women, data were still too sparse to evaluate some important variables. Even within GOG protocols with uniform eligibility requirements, outcomes are more favorable for white patients [18].…”
Section: Racial Disparitiesmentioning
confidence: 99%